Pendapatan Negara Antara Konvensional Dan Islam - Aqif Khilmia; Mustofa Mustofa (Al-Buhuts, 2022)
The purpose of this study is to understand the significant differences between the pattern of state income in conventional and in Islam. The research method used is library research with a descriptive approach. That is describing state income between conventional and Islamic. Sources are taken from various references related to the topic of the problem, namely from books, journals, and other articles. The results of the study conclude that national income in the conventional concept states GDP or Real GNP can be used as a measure of economic welfare (Measure of Economic Welfare). In contrast to Muslim economists, that there are 4 indicators that can be used as a benchmark for community welfare, namely measuring the distribution of household income, production in the rural sector, the welfare of the Muslim community, and the calculation of national income as a measure of Islamic socio-economic welfare. Sources of national income from an Islamic economic perspective include ghanimah, zakat, alms, infaq, ushr, jizyah, kharaj, mining taxes, and waqf. Because these instruments have a very large impact on the welfare of the community.